The influence of leverage, sales growth, and dividend policy on company value - Ratu Liviani; Yoga Tantular Rachman (International Journal of Financial, Accounting, and Management, 2021)
Purpose: This study aimed to determine whether leverage, sales growth, and dividend policies influence the value of the company and determine the development of leverage, sales growth, dividend policy, and company value in real estate, property, and construction companies listed on the Stock Exchange Indonesia period of 2016-2018 Research methodology: This research was a quantitative research. The samples were real estate, property and building construction sector companies listed on the Indonesia Stock Exchange for the period of 2016-2018, amounting to 20 companies. The sampling technique used was non probability sampling with a purposive sampling method.. Results: Leverage, sales growth, and dividend policy affect the company value. The magnitude of the influence of leverage, sales growth, and dividend policy in contributing influence of company value was 58.0%. Limitations: The research is limited to only those companies in the real estate, property, and building construction sectors listed on the Indonesia Stock Exchange from 2016 to 2018 and only focuses on the effect of leverage, sales growth, and dividend policy on firm value. Contribution: Companies in the real estate, property, and building construction sectors listed on the Indonesian Stock Exchange should reduce their leverage, increase sales growth by improving their performance in selling products or services, and improve their dividend policy by increasing dividend distribution to shareholders each year.